Analysis of plasma termination in the JET hybrid scenario. (12th June 2018) - Hobirk, J.; Bernert, M.; Buratti, P.; Challis, C.D.; Coffey, I.; Drewelow, P.; Joffrin, E.; Mailloux, J.; Nunes, I.; Pucella, G.; Pütterich, T.; de Vries, P.C.
Abstract: This paper analyses the final phase of hybrid scenario discharges at JET, the reduction of auxiliary heating towards finally the Ohmic phase. The here considered Ohmic phase is mostly still in the current flattop but may also be in the current ramp down. For this purpose a database is created of 54 parameters in 7 phases distributed in time of the discharge. It is found that the occurrence of a locked mode is in most cases preceded by a radiation peaking after the main heating phase either in a low power phase and/or in the Ohmic phase. To gain insight on the importance of different parameters in this process a correlation analysis to the radiation peaking in the Ohmic phase is done. The first finding is that the further away in time the analysed phases are the less the correlation is. This means in the end that a good termination scenario might also be able to terminate unhealthy plasmas safely. The second finding is that remaining impurities in the plasma after reducing the heating power in the termination phase are the most important reason for generating a locked mode which can lead to a disruption.